Alkaloids and Selected Topics in Their Thermochemistry - Maja Ponikvar-Svet (MDPI AG, 2021)
Alkaloid chemistry is varied and complex. Many alkaloids attract a great deal of interest because of their physiological activity, yet surprisingly little is known about the thermochemistry of these compounds, especially in the gas phase. In this paper, we investigate the thermochemical characteristics, specifically demethoxylation enthalpies rather than those derived from trans-methoxylation reactions, of a series of biologically relevant alkaloids in their condensed phase.